Surgical-orthodontic therapy of compound odontoma in the anterior maxilla - Bruna Cristina Longo; Lais Kuhn; Maria de Fátima M. Tomasin; Amadeu Tomasin Neto; Geraldo Grizza; Maria Daniela B. Souza
abstract Odontomas are odontogenic tumors subdivided into complex type (common in the posterior mandible region) and compound type. These lesions are usually asymptomatic and diagnosed in routine examinations, are more frequent in the second decade of life. The objective of this case is to report the treatment of a patient with complex odontoma in childhood in the anterior maxilla. A nine-year-old patient sought dental care due to non-eruption of an anterior permanent tooth. After clinical examination and radiographic analysis, the diagnostic hypothesis of odontoma was confirmed. Surgical removal of the lesion and use of orthodontic appliances were indicated. After the therapeutic protocol, the case was completely resolved. Due to the absence of symptoms, many cases of odontomas are neglected. However, it is evident that the sooner diagnosed, the better the prognosis of the patient.